THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, EMPLOYEE INVOLVEMENT, AND ORGANIZATIONAL CULTURE ON EMPLOYEE COMPETENCE AT PT. TASPEN (PERSERO) KCU JAKARTA - Meindro Waskito (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
This study aimed to examine the influence of transformational leadership, employee involvement, and organizational culture on employee competence at PT. Taspen (Persero) KCU Jakarta. The research method used was a quantitative approach with a survey method. The sample used in this study was 123 employees at PT. Taspen (Persero) KCU Jakarta. The data collected was analyzed using multiple regression analysis through SPSS version 25 software. The results showed that employee involvement through organizational culture had an indirect path coefficient of 0.053 at a significance level of ? = 5% and had a t count of 1.834 > table of 1.645, which meant there was a significant positive effect between employee involvement through organizational culture on employee competence. Furthermore, transformational leadership and organizational culture had a significant positive effect on employee competence. The results of this study can be used as a reference for the company to improve employee competence through transformational leadership, employee involvement, and organizational culture.